Good Grief - Westberg, E,Granger (Philadelphia Fortress Press, 1971)
Here is a volume to be kept close at hand. It can be used over the years as you encounter a wide variety of grief experiences or as you assist friends in moving beyond grief to "good" grief.
twenty-seventh printing 1989
Keywords: Grief. Consolation. Grief. Christian life -- History -- 20th century